2012
DOI: 10.1371/journal.pone.0035387
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Expression of Phosphorus (P) Responsive Genes in Cucumis melo L

Abstract: BackgroundPhosphorus (P) is a major limiting nutrient for plant growth in many soils. Studies in model species have identified genes involved in plant adaptations to low soil P availability. However, little information is available on the genetic bases of these adaptations in vegetable crops. In this respect, sequence data for melon now makes it possible to identify melon orthologues of candidate P responsive genes, and the expression of these genes can be used to explain the diversity in the root system adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…PEPC-malate dehydrogenase-malic enzyme glycolytic bypass, which reduces the requirement for Pi, is a well-documented alteration of glycolysis under Pi starvation [11]. Up-regulation of PEPC and PPCK by P deficiency has been documented in Arabidopsis, rice, white lupin, orange, and melon [12,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…PEPC-malate dehydrogenase-malic enzyme glycolytic bypass, which reduces the requirement for Pi, is a well-documented alteration of glycolysis under Pi starvation [11]. Up-regulation of PEPC and PPCK by P deficiency has been documented in Arabidopsis, rice, white lupin, orange, and melon [12,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying cause for this is the elongation of roots in C1 treatment, a possible strategy of adaptation to low availability of P in the soil (Fita et al, 2012). Research, Society and Development, v. 9, n. 7, e973974560, 2020(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4560 Meng et al (2014 classified seven genotypes of watermelon with regard to responsiveness and P use efficiency and observed that the capacity of P absorption by the plants correlated with the morphological traits of roots.…”
Section: Sv¹mentioning
confidence: 99%
“…One factor that affects root growth is the availability of phosphorus (P) for plants, to which the latter respond in the form of adaptations in root system morphology and architecture (Fita et al, 2012;Meng et al, 2014) as well as in the partition of assimilates between the roots and the aerial part (Marschner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Melon (Cucumis melo L.) is a highly diversi ed eudicot diploid (2n = 2x = 24) cucurbitaceous crop with a genome size of approximately 375 Mb [1]. Melon is economically important and ranks as the 9 th most cultivated horticultural crop in terms of worldwide production [2,3]. Its sweet, musky-avored, eshy fruit is rich in vitamins, minerals, and health-promoting antioxidants, including ascorbic acid, carotene, folic acid, and potassium [4][5][6].…”
Section: Introductionmentioning
confidence: 99%